Hybrid energy system models - Berrada, Asmae; El Mrabet, Rachid (Academic Press, 2021)
Hybrid Energy System Models presents a number of techniques to model a large variety of hybrid energy systems in all aspects of sizing, design, operation, economic dispatch, optimization and control. The book's authors present a number of new methods to model hybrid energy systems and several renewable energy systems, including photovoltaic, solar plus wind and hydropower, energy storage, and combined heat and power systems. With critical modeling examples, global case studies and techno-economic modeling integrated in every chapter, this book is essential to understanding the development of affordable energy systems globally, particularly from renewable resources. With a detailed overview and a comparison of hybrid energy systems used in different regions, as well as innovative hybrid energy system designs covered, this book is useful for practicing power and energy engineers needing answers for what factors to consider when modeling a hybrid energy system and what tools are available to model hybrid systems. Combines research on several renewable energy systems, energy storage, and combined heat and power systems into a single informative resource on hybrid energy systems Includes significant global case studies of current and novel modeling techniques for comparison Covers numerical simulations of hybrid systems energy modeling and applications.